A Theory of Interindustry Wage Structure Variation - Garbarino, Joseph W. (Quarterly Journal of Economics, 1950)
I. Introduction, 282. — II. Productivity and the Wage Structure, 282. — III. Unionism and Earnings, 285. — IV. Variation in the Wage Structure, 290. — V. The Statistical Evidence, 1923–1940, 295. — VI. Conclusion, 305.